Clinical Utility of Long-Acting Injectable Risperidone in Schizophrenia and Bipolar I Disorder: A Review of Clinical Studies - Bartoli F; Cavaleri D; Riboldi I; Capogrosso CA; Carrà G (Psychology Research and Behavior Management)
Francesco Bartoli, Daniele Cavaleri, Ilaria Riboldi, Chiara Alessandra Capogrosso, Giuseppe Carr&#x00E0School of Medicine and Surgery, University of Milano-Bicocca, Monza, 20900, ItalyCorrespondence: Daniele Cavaleri, School of Medicine and Surgery, University of Milano-Bicocca, via Cadore 48, Monza, 20900, Italy, Tel +39 02 6448 8326, Email d.cavaleri1@campus.unimib.itAbstract: Risperidone was the first second-generation antipsychotic to be developed as a long-acting injectable (LAI). In the early 2000s, a risperidone microsphere formulation, intramuscularly administered every 2 weeks (BW-RLAI), was introduced. To date, five different risperidone LAI formulations have been marketed – including a second biweekly microsphere injection (LY03004), a newer monthly intramuscular formulation using in situ microparticles (ISM) technology that does not require an oral risperidone run-in, and two subcutaneous formulations (RBP-7000 and TV-46000). Understanding the advantages and limitations of each option is essential for tailoring treatment regimens based on clinical needs and patient preferences. In this review, with the aim of offering insights for clinical practice and future research, we provide a comprehensive synthesis of the currently available risperidone LAI formulations, examining their efficacy and safety for the treatment of schizophrenia and bipolar I disorder. While evidence supporting the efficacy, tolerability, and safety of risperidone LAI for schizophrenia is available for all marketed formulations to date, advantages for newer formulations, such as longer dosing intervals without oral supplementation, are also reviewed. In addition, although the Food and Drug Administration approved the biweekly LAIs for bipolar I disorder, there is no data on effectiveness of the other risperidone LAI formulations for this indication so far. The variety of the available risperidone LAI options is likely to enable a more personalized treatment approach. To facilitate this, healthcare providers should develop a comprehensive understanding of these formulations to select the most suitable option. While risperidone ISM, RBP-7000, and TV-46000 may enhance treatment feasibility and adherence, further research is needed to build an evidence base comparable to that available for BW-RLAI, particularly in the treatment of BD.Plain Language Summary: Risperidone is a second-generation antipsychotic used to treat schizophrenia and bipolar I disorder. It was the first drug of its class to be made available as a long-acting injectable (LAI), offering continuous treatment without the need for daily pills. Over time, several risperidone LAI formulations have been developed, including biweekly and monthly intramuscular injections – such as risperidone microspheres and risperidone in situ microparticles (ISM) – as well as subcutaneous options available exclusively in the United States. This review provides an updated overview of the efficacy and safety of all currently available risperidone LAI formulations for the treatment of schizophrenia and bipolar I disorder.Each formulation has distinct advantages and limitations: for instance, some require an initial period of oral risperidone supplementation, while others do not; some allow for longer dosing intervals, reducing the frequency of injections. Selecting the most appropriate option depends on both clinical needs and patient preferences.While all approved risperidone LAI formulations have demonstrated their role in treating schizophrenia, only the biweekly risperidone microsphere formulation has been officially approved for bipolar I disorder. Further research is needed to assess the effectiveness of other formulations for this condition.A thorough understanding of these options can help clinicians provide more personalized and effective treatment for individuals with schizophrenia and bipolar I disorder. Keywords: bipolar disorder, effectiveness, long-acting injectables, RBP-7000, review, risperidone, risperidone ISM, risperidone microspheres, schizophrenia, TV-46000